Dalail Al-Khairat sebagai Strategi Pengembangan Kecerdasan Spiritual Santri Putri di Pesantren Annuqayah Lubangsa Utara - Khoir, Ummal; Muttaqin, Jamalul (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
Spiritual intelligence has become a critical concern in contemporary Islamic education amid the challenges of modern civilization that increasingly alienate individuals from their spiritual identity. This study aims to examine the implementation of Dalail Al-Khairat recitation as a strategy for developing the spiritual intelligence of female students at Pesantren Annuqayah Lubangsa Utara Putri. Employing a qualitative field research design, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using descriptive-qualitative techniques. Grounded in Danah Zohar and Ian Marshall's framework of spiritual intelligence, the findings reveal two key conclusions. First, the Dalail Al-Khairat recitation program is a mandatory institutional initiative established by the pesantren caregiver and coordinated by the Ta'mir and Peribadatan division, conducted every Friday Legi from approximately 7:00 to 10:00 a.m. Second, students who participate regularly demonstrate measurable indicators of enhanced spiritual intelligence, including a heightened sense of inner calm in facing adversity, God-centered motivation in daily conduct, full conscious awareness in every action, and a stable set of life principles and values. These findings contribute empirical evidence that structured religious practice, when institutionally embedded within the pesantren curriculum, constitutes an effective pedagogical strategy for holistic spiritual development. This study underscores the strategic role of traditional Islamic devotional practices in addressing the spiritual crisis of contemporary youth.